1, 4‐Cyclohexadienes—Easy Access to a Versatile Building Block via Transition‐Metal‐Catalysed Diels–Alder Reactions. Issue 3 (30th May 2014) - Hilt, Gerhard
Abstract 1, 4‐Cyclohexadiene derivatives are easily accessed via transition‐metal cycloadditions of 1, 3‐dienes with alkynes. The mild reaction conditions of several transition‐metal‐catalysed reactions allows the incorporation of various functional groups to access functionalised 1, 4‐cyclohexadienes. The control of the regiochemistry in the intermolecular cobalt‐catalysed Diels–Alder reaction is realised utilising different ligand designs. The functionalised 1, 4‐cyclohexadiene derivatives are valuable building blocks in follow‐up transformations. Finally, the oxidation of the 1, 4‐cyclohexadienes can be accomplished under mild conditions to generate the corresponding arene derivatives.